AN EXPLANATORY INVESTIGATION ON FOREIGN LANGUAGE ANXIETY AMONG ENGLISH DEPARTMENT STUDENTS AT STKIP PGRI LAMPUNG - Nuryansyah Adijaya; M. Natsir Amir; M. Sofian Hadi (Indonesian EFL Journal, 2026)
In the context of globalized English education, university students frequently encounter emotional and psychological barriers that hinder their mastery of English as a foreign language. One such barrier is Foreign Language Anxiety (FLA), which has been shown to significantly affect learners’ confidence, performance, and overall language acquisition. This study investigates the existence and sources of FLA among English Department students at STKIP PGRI Lampung, employing a quantitative descriptive design. Data were collected using Horwitz, Horwitz, and Cope’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS), which measures four domains of anxiety: communication apprehension, test anxiety, fear of negative evaluation, and general classroom anxiety. Findings revealed that the majority of students reported moderate levels of anxiety, with test anxiety and general classroom anxiety identified as the most influential contributors to heightened stress in English learning contexts. The study concludes with pedagogical implications and recommendations for reducing FLA in Indonesian higher education settings.